Upaya Meningkatkan Pemasaran Digital UKM Sekar Madu Melalui Pemanfaatan Teknologi Digital Dengan Video Branding - Ariwangsa, I G. N Oka; Apriliani, Ni Putu Mia; Laksmi, Kadek Wulandari; Putra, Komang Satria Wibawa (LPPM Universitas Trunojoyo Madura, 2023)
Due to the impact of the COVID-19 pandemic and less than optimal management of digital marketing strategies, Sekar Madu SMEs experienced a decrease in sales volume and decreased revenue. Therefore, the solution that can be offered to the owner is to use digital marketing strategies through social media and utilize digital technology by making branding videos at Sekar Madu SMEs to support digital marketing in the hope of increasing sales volume and profits. This community service activity aims to help the owner of Sekar Madu SMEs in terms of improving their business marketing through social media by utilizing digital technology, namely making branding videos that will help introduce a product in a wider range through social media, to increase sales volume and profits. The methods used in community service activities are observation, interviews, and documentation in the form of applying digital technology by making branding videos. The result of this community service activity is that the owners of Sekar Madu SMEs begin to understand current, correct and effective branding, promotion or marketing strategies, and have the awareness to continue to innovate in terms of digital promotion or marketing through social media.